The impact of minimum wage policy on hours of work, happiness and quality of life: The perception of employees in the rubber estates of Kedah, Malaysia - Thilagavathi, Muttu (2015)
This study aims to investigate the relationship between hours of work, quality of life, and happiness with success of Minimum Wage Policy implementation among rubber estates employees in the agricultural sector. The relationship between those variables are predicted based on relevant literature, and are tested using survey results from 66 respondents or rubber estates employees in Kedah. Descriptive statistics analysis used to analyse the corresponding characteristics of the sample. Reliability of measures is established by testing for both consistency and stability. Pearson‟s Correlation used to test the relationships between minimum wage and hours of work, minimum wage and happiness, and minimum wage and quality of life. Overall results indicated that all the independent variables such as hours of work, happiness, and quality of life were significant influences by the Minimum Wage Policy. It can be observed that minimum wage is positively correlated with hours of work, happiness and quality of life. It also can be concluded that there is a small shock effect of minimum wage policy on hour of work and quality of life and a big shock effect of minimum wage policy on happiness. Moreover, the findings of this study can encourage the government to appreciate the effects of the minimum wage policy and ensure adequate monitoring with the aim of allowing estates adjust and minimize adverse effects on hours of work, happiness, and quality of life of employees. Moreover, it also will provide a useful guidance to the policy makers of other developing countries in implementation a new policy for future development especially in the agricultural sector